Ex vivo microscopic testicular sperm extraction at the time of radical orchiectomy in men with nonobstructive azoospermia (NOA): a scoping review - Carlo Giulioni; Nguyen Ho Vinh Phuoc; Selahittin Cayan (Asian Journal of Andrology)
Testicular tumor is the most common solid malignancy in males under 40 years of age. This malignancy is known to have a negative impact on male fertility. Therefore, several techniques for sperm retrieval have been proposed, including microdissection testicular sperm extraction (mTESE). The objective of this study was to review the literature on the outcomes of oncological (Onco)-mTESE at the time of radical orchiectomy. We conducted a comprehensive literature search through PubMed, Scopus, and Cochrane Central Controlled Register of Trials. Only studies reporting ex vivo mTESE in patients with testicular tumor were considered. Twelve papers met the inclusion criteria and were included in this review. Tumor size was identified as the sole preoperative factor influencing spermatogenesis. The considered studies demonstrated a satisfactory success rate for Onco-mTESE, associated with a similarly valid percentage of live healthy births through assisted reproductive technology. Currently, no comparison has been made between Onco-mTESE and conventional Onco-TESE, hence further assessment is required. In cases where the tumor completely replaces the cancer-bearing testicle, a contralateral micro-TESE may be a viable alternative. However, the surgeon should evaluate associated risks and benefits preoperatively. In conclusion, Onco-mTESE at the time of radical orchiectomy appears to be a promising therapeutic option for young patients with testicular tumors. Nevertheless, additional studies are necessary to achieve a definitive conclusion.